Evaluation of long‐acting cabotegravir safety and pharmacokinetics in pregnant women in eastern and southern Africa: a secondary analysis of HPTN 084 - Sinead Delany‐Moretlwe; Brett Hanscom; Xu Guo; Clemensia Nkabiito; Patricia Mandima; Patricia Ntege Nahirya; Juliet Mpendo; Muchaneta Bhondai‐Mhuri; Nyaradzo Mgodi; Rebecca Berhanu; Jennifer Farrior; Estelle Piwowar‐Manning; et al. (Journal of the International AIDS Society)
Abstract Introduction Long‐acting injectable cabotegravir (CAB‐LA) for pre‐exposure prophylaxis significantly reduced HIV acquisition in HPTN 084. We report on the safety and CAB‐LA pharmacokinetics in pregnant women during the blinded period of HPTN 084. Methods Participants were randomized 1:1 to either active cabotegravir (CAB) plus tenofovir disoproxil fumarate/emtricitabine (TDF/FTC) placebo or active TDF/FTC plus CAB placebo. Pregnancy testing was performed at each visit; participants with a positive test had study product withheld and were offered open‐label TDF/FTC. Pregnancies were confirmed on two tests at least 4 weeks apart. All participants with a positive pregnancy test prior to November 5, 2020 are included in this analysis. Pregnancy incidence, maternal adverse event (AE) incidence, pregnancy outcomes (including composite outcome of spontaneous abortion <20 weeks, intrauterine foetal death or stillbirth ≥20 weeks, premature birth <37 weeks, or small for gestational age) were assessed. The apparent terminal phase half‐life (t1/2app) of CAB‐LA in pregnant women in HPTN 084 was compared to non‐pregnant women from the phase 2a HPTN 077 trial. Multivariable models assessed associations with t1/2app. Results Fifty‐seven pregnancies (30 CAB‐LA, 27 TDF/FTC) were confirmed over 3845 person‐years [py] (incidence 1.5/100 py, 95% CI 1.1−1.9). CAB‐LA group participants had a median 342 days (IQR 192, 497) of CAB‐LA exposure prior to pregnancy detection. Grade 2 or higher maternal AE incidence did not differ by study arm (CAB 157, 95% CI 91−271 per 100 py vs. TDF/FTC 217, 95% CI 124–380 per 100 py; p = 0.256). Most pregnancies (81%) resulted in live births (25 CAB‐LA, 22 TDF/FTC). Composite poor pregnancy outcomes did not differ significantly by group (CAB 6/30 vs. TDF/FTC 4/27; p = 0.476). No congenital anomalies were observed. The CAB t1/2app geometric mean was 52.8 days (95% CI 40.7−68.4) in pregnant women compared to 60.3 days (95% CI 47.7−76.3; p = 0.66) in non‐pregnant women; neither pregnancy nor body mass index were significantly associated with t1/2app. Conclusions CAB‐LA concentrations post‐cessation of injections were generally well tolerated in pregnant women. The t1/2app was comparable between pregnant and non‐pregnant women. Ongoing studies will examine the safety and pharmacology of CAB‐LA in women who choose to continue CAB‐LA through pregnancy and lactation.